2014
DOI: 10.1159/000357617
|View full text |Cite
|
Sign up to set email alerts
|

UVA-Photoactivated Riboflavin Treatment of Vaginal Cells Derived from Pelvic Organ Prolapse Cases

Abstract: Background: The pathophysiology of pelvic organ prolapse (POP) involves vaginal collagen degradation. Strengthening collagen by UVA-photoactivated cross-linking has been demonstrated and suggested target applications include the vaginal wall. Aim: To identify UVA irradiation and riboflavin effects on vaginal cells. Materials and Methods: Vaginal cells were incubated for 24 h (DMEM/F-12 Ham's media) and were exposed to riboflavin (0, 0.1 and 10%) for 30 min before UVA photoactivation. Percentages of live, apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The reduction of cell viability after UVA treatment and their increment after RF treatment, has been already demonstrated by Schultz et al in vaginal connective tissue cells [ 28 ]. Schultz et al tried to clarify viability, apoptosis and necrosis of vaginal cells treated by RF and UVA-based photopolymerization in order to strengthen vaginal tissues at risk of prolapse.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The reduction of cell viability after UVA treatment and their increment after RF treatment, has been already demonstrated by Schultz et al in vaginal connective tissue cells [ 28 ]. Schultz et al tried to clarify viability, apoptosis and necrosis of vaginal cells treated by RF and UVA-based photopolymerization in order to strengthen vaginal tissues at risk of prolapse.…”
Section: Discussionmentioning
confidence: 86%
“…To achieve this goal, vaginal cells were exposed to different concentrations of RF (0.1 and 10%) and control medium, followed by UVA irradiation (3 mW/cm 2 ). They showed that RF attenuated UVA-related phototoxicity and damage by inhibiting necrosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, riboflavin (7) and synthetic derivatives are photoactive, as shown by their ability to produce singlet oxygen under irradiation [63]. Nevertheless, photoprotective properties were also demonstrated for riboflavin [64], thus riboflavin's phototoxicity seems strongly concentration and irradiation dependent. Riboflavin (7) can be isolated from several higher fungi [65], as for example from Calocybe chrysenteron [66] or Russula xerampelina (η = 12.6% DW) [67].…”
Section: Alkaloidsmentioning
confidence: 99%